Analisis Sub Sektor Perkebunan Pala di Provinsi Sulawesi Utara - Soraya ., Pangalima; Caroline B.D. Pakasi; Noortje M. Benu (AGRI-SOSIOEKONOMI, 2016)
The purpose of this research is to analyze the nutmeg plantation sub sector in North Sulawesi Province. These research ongoing 3 month begun from August 2015 until October 2015, starting from the pre-preparation until the preparation of research results. The examination took place in the Province of North Sulawesi. The data using in this research i.e. secondary data. Secondary data gained from the land of North Sulawesi province, to observe the production of Nutmeg in North Sulawesi province and sampling in two locations as largest nutmeg producing in North Sulawesi province knowing as Sitaro Islands Regency and North Minahasa Regency. Data examination in research using analysis of LQ (Location Quotion) and analysis of Shift Share.The results of research showing that LQ nutmeg commodity in the North Minahasa Regency in 2010-2014 > LQ value is 1, the value of Proportional Shift and Differential Shift Nutmeg commodity in North Minahasa Regency is located in Group II (Proportional Shift negative and Differential Shift positive) group that is growing (developing). nutmeg LQ of Sitaro Islands Regency in 2010-2014 LQ value nutmeg Commodity has a value > 1. Based on the value of Proportional Shift and Differential Shift Nutmeg commodity in the North Minahasa Regency is a group II (Proportional Shift negative and Differential Shift positive) group that is growing (developing).